Childhood non-Hodgkin lymphomas in the United Kingdom: findings from the UK Children's Cancer Study Group. Issue 2 (February 1997) - Wright, D; McKeever, P; Carter, R
Abstract : AIM: To review the presenting clinical features and the histology of cases of non-Hodgkin lymphoma (NHL) entered into the United Kingdom Children's Cancer Study Group NHL Trial. METHODS: Sections of biopsy specimens from all cases entered into the trial were stained with Giemsa and haematoxylin and eosin. All cases were stained immunohistochemically for CD45, CD3, CD45RO, CD20, and CD30. Sections were stained with either naphthol AS-D chloroacetate esterase or KP1 (CD68) to identify granulocytic tumours. In a minority of cases, additional immunohistochemical stains were performed when necessary to establish the diagnosis. The sections were reviewed by three pathologists. RESULTS: Of 308 cases analysed, 293 were categorised as NHL. There was only one case of low grade lymphoma in the series. Over 80% of the cases fell into the categories Burkitt lymphoma (42.2%), lymphoblastic lymphoma (27.2%) and anaplastic large cell lymphoma (15.1%). Cases of Burkitt lymphoma presented most often with abdominal tumours mainly of the ileocaecal region. Tumours of the oropharynx and nasopharynx were also common in this group. Of the 84 lymphoblastic lymphomas, 56 were of the T-cell phenotype, 12 of the B-cell phenotype and 16 of indeterminate lineage. Most of the T-lymphoblastic lymphomas showed mediastinal or pleural involvement. Infiltration of the skin and soft tissues was seen in 25% of lymphoblastic lymphoma of B or indeterminate phenotype. Forty six children were diagnosed as having anaplastic large cell lymphoma, the majority being of T or indeterminate lineage. Most patients presented with lymphadenopathy but involvement of the bones, soft tissues or skin was seen in seven patients and of the mediastinum and lungs in five. CONCLUSION: Childhood non-Hodgkin lymphomas are almost all high grade and frequently extranodal. They fall mainly into the categories Burkitt lymphoma, lymphoblastic lymphoma and anaplastic large cell lymphoma. The separation of these subcategories can be made on the basis of morphology and immunohistochemical features. The anatomical distribution of these different categories of non-Hodgkin lymphoma is distinctive.